Forming Geographic Knowledge - Inna Shorobura (Pedagogical Discourse, 2014)
The problem of beginning of studying geographic knowledge on the territory of Ukraine has been cleared up in the article. The history of school geographic education is an important component of general history of pedagogics. Acquaintance with its forming allows us not only to comprehend general picture of its development in Ukraine as an integral, multifaceted phenomenon, but also creates conditions for the system reproduction of the domestic historic-pedagogical process. Construction of geography courses on the territory of Ukraine has been analyzed. The problems of studying geographic knowledge and possible ways to solve them have been covered. For the first time the elements of natural knowledge were taught at schools in the XVII century. In the XVIII century gradually some elements of school geographic education were formed, including the list of questions and ideas of geographic science, which was the part of natural science or the separate subject. During the century both translated and domestic textbooks on geography appeared and gradually perfected. We can see attempts to work out methodological techniques to teach geography. In the XVIII century the premises for the forming such integral pedagogical phenomenon as school geographic education appeared.